Teaching vocabulary through interaction in the eighth grade basic education in secondary schoools of Azogues - Mendoza Ortega, Marisol; Castro González, Víctor
This paper provides a framework with abundant ideas and material oriented to help people involved in teaching or learning English as a second or foreign language. Though relevant research has been done for centuries, there are and there will be always room for improvement, adaptations, and changes of methods, techniques and strategies, provided that language, itself, is a living being and, therefore, the basic components of its corpus, words, come into light, become part of the corpus, and then die. We emphasize on the importance of teaching vocabulary through schematic and well-documented information. As a result of an extensive bibliography, some field research, and our own experimentation we have come to the conclusion that all the above-cited sources reveal the necessity to improve the methodology to teach vocabulary by giving students the opportunity of being spontaneous with their written and spoken language, which allows them to become starring participants of the teaching learning process. Further on, our thesis statement points out to detailed literature on language classroom interaction, so that readers can understand thoroughly the role and scope of classroom interaction, which is expected to be applied in the language- learning process. In so doing, English teachers will perceive that self-confidence, motivation, and free-expression will flow from the learner?s skills. Likewise, our thesis pioneers a range of activities to promote creativity, which results in conscious or unconscious learners and teachers? engagement that sets them in the route of constant research and creativity, given that language teaching is a never-ending task.